Analysis of Local Regional Potential Empowerment as a Learning Resource in the Project for Strengthening the Profile of Pancasila Students (P5) - Asera, Gesti Ayu Diah; Riyadi, Riyadi; Suryandari, Kartika Chrysti (Universitas Sebelas Maret, 2024)
This research focuses on empowering local regional potential as a source of P5 learning in elementary schools. This research uses a qualitative approach with a descriptive research design. Data collection was carried out using observation techniques, in-depth interviews with informants using snowball sampling, and documentation. Data analysis was carried out by applying a descriptive qualitative interactive model approach through the steps of data collection, data reduction, data presentation, verification and drawing conclusions. The research results show that the planning stages carried out in empowering local regional potential as a P5 learning resource are choosing a theme, choosing a coordinator, forming a team, determining a supervisory team, determining a topic, determining implementation time, and developing modules. Implementation of the use of local regional potential as a P5 learning resource is carried out in the form of Cultural Saturday programs and market days which display products from local agricultural and plantation products. Evaluation of the empowerment of local potential as a P5 learning resource pays attention to input and process aspects that focus on daily assessments and periodic assessments to obtain responses from teachers and students, and determine follow-up plans.